Fenomena jerebu rentas sempadan - Abdul Rahim Abdul Samad; Penerbit Universiti Putra Malaysia (Serdang : Penerbit Universiti Putra Malaysia, 2021)
On transboundary seasonal haze in Malaysia and sorrounding countries, and its impact on health.
Includes bibliographical references (pages 57-61) and index.
In Malay.
Keywords: Air -- Pollution -- Malaysia; Air -- Pollution -- Health aspects -- Malaysia; Haze -- Environmental aspects -- Malaysia